Pengaruh Parental Social Media Mediation terhadap Perilaku Cyberbullying - Kennisza Rizalda; Sulisworo Kusdiyati (UNISBA Press, 2023)
Abstract. The use of the internet, especially social media, has changed the way teenagers communicate and socialize. While there are benefits to living in a digital world, there are also risks involved, one of which is cyberbullying. One of the factors that influence cyberbullying is the duration spent online. To reduce the risk of excessive online activity, parents carry out mediation strategies. The purpose of this study is to find out how the description and influence of parental social media mediation on cyberbullying behavior in junior high school adolescents in West Java Province. In this study, using the parental social media mediation scale (PSMMS) from Ho et al. (2019) and a cyberbullying offending scale from Patchin & Hinduja (2015). This research was conducted on 169 junior high school teenagers in West Java province using causality and purposive sampling methods. This study uses multiple linear regression test and the R-Square result is 0.116. Parental social media mediation contributes to cyberbullying behavior by 11.6%.Abstrak. Penggunaan internet, terutama media sosial telah mengubah cara remaja berkomunikasi dan bersosialisasi. Meskipun terdapat manfaat untuk hidup di dunia digital, terdapat juga risiko yang dapat terlibat, salah satu risikonya adalah tindakan cyberbullying. Salah satu faktor yang mempengaruhi tindakan cyberbullying adalah durasi yang dihabiskan untuk online. Untuk mengurangi risiko aktivitas online berlebihan, orang tua melakukan strategi mediasi. Tujuan penelitian ini yaitu untuk mengetahui bagaimana gambaran dan pengaruh parental social media mediation terhadap perilaku cyberbullying pada remaja SMP di Provinsi Jawa Barat. Pada penelitian ini menggunakan alat ukur parental social media mediation scale (PSMMS) dari Ho et al. (2019) dan alat ukur cyberbullying offending scale dari Patchin & Hinduja (2015). Penelitian ini dilakukan kepada 169 remaja SMP di provinsi Jawa Barat dengan menggunakan metode kausalitas dan purposive sampling. Penelitian ini menggunakan uji regresi linear berganda dan didapat hasil R-Square sebesar 0,116. Parental social media mediation berkontribusi terhadap perilaku cyberbullying sebesar 11,6%.